2017
DOI: 10.3892/ol.2017.7683
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of monoamine oxidase A is associated with epithelial to mesenchymal transition and clinicopathological features in non-small cell lung cancer

Abstract: Abstract. Monoamine oxidase A (MAOA), a mitochondrial enzyme, is closely associated with neurological disorders. Recently, MAOA has been linked to the progression of prostate cancer, hepatocellular carcinoma, and cholangiocarcinoma. However, MAOA was reported to have different effects on the progression of these types of cancer, and the role of MAOA in non-small cell lung cancer (NSCLC) progression remains unclear. The present study determined the expression of MAOA and epithelial to mesenchymal transition (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…When the HIF-1 pathway is upregulated, vascular endothelial growth factor, epithelial-mesenchymal transition and membrane-type 4 matrix metalloproteinase are activated (27)(28)(29). In the present study, DMOG treatment alone for 48 h was able to promote the colony-forming and migrating ability of HCC827 cells (Figs.…”
Section: Discussionsupporting
confidence: 51%
“…When the HIF-1 pathway is upregulated, vascular endothelial growth factor, epithelial-mesenchymal transition and membrane-type 4 matrix metalloproteinase are activated (27)(28)(29). In the present study, DMOG treatment alone for 48 h was able to promote the colony-forming and migrating ability of HCC827 cells (Figs.…”
Section: Discussionsupporting
confidence: 51%
“…The report that MAOA promoted NSCLC progression by mediating EMT raised an intriguing question of whether MAOA could serve as a therapeutic target in NSCLC treatment. 15 In this study, we used a previously synthesized compound, G11, whose in vitro antitumor efficacy and MAOA inhibitory ability have been confirmed in human prostate cancer cells. Through cytotoxicity evaluation and MAOA activity assay, we found that MAOA activities were relatively higher in paclitaxel-resistant NSCLC cells than in parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] A recent research result indicated that nonsmall cell lung cancer (NSCLC) tissues exhibited upregulation of MAOA compared with surrounding normal lung tissues. 15 Furthermore, a close relationship has been observed between increased MAOA expression in NSCLC tissues and Slug, N-cadherin and TWIST expression, EMT and the development of clinicopathological features of NSCLC such as later stage and lymph node metastasis. These findings suggest that MAOA may promote NSCLC progression by inducing EMT.…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC tissue specimens were collected from 45 patients with NSCLC in Affiliated Hospital of Guangdong Medical University (Zhanjiang, Guangdong, China) from 2007 to 2010. Meanwhile, the matched non-tumor adjacent lung tissues (1 cm from NSCLC tissues) were obtained from the same patients 37 . The criteria that patients should be met were according to our previous study 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the matched non-tumor adjacent lung tissues (1 cm from NSCLC tissues) were obtained from the same patients 37 . The criteria that patients should be met were according to our previous study 37 . This study was received the ethic approval from the local committee of Affiliated Hospital of Guangdong Medical University, and all clinical studies were performed according to the principles defined by the Declaration of Helsinki 37 .…”
Section: Methodsmentioning
confidence: 99%